The environmental determinants of disease transmission in Medan City - Hasibuan, Elisa Khairiyah; Silalahi, Marlinang Isabella; Hartono, Hartono (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Health issues, potentially triggered by environmental conditions and human behaviour, represent a complex challenge, particularly in Indonesia where environmentally related diseases remain a primary cause of mortality. This study aimed to ascertain the spatial distribution of Dengue Haemorrhagic Fever (DHF), Tuberculosis (TB), and diarrhoea in the city of Medan. The research employed a descriptive analysis of DHF and TB case data aggregated by sub-district, encompassing population, age group, and sex distribution. Acute diarrhoea case data were collected from various community health centres (puskesmas) in Medan City, categorized by puskesmas location, patient age, and dehydration status. The results revealed significant variations in the number of DHF cases across Medan's sub-districts, with Medan Helvetia recording the highest incidence. The distribution of TB cases also varied, with Medan Deli exhibiting the highest number of reported cases. For diarrhoea, Puskesmas Helvetia reported the highest number of cases. The discussion delves into the factors influencing the spatial distribution of these three diseases, including population density, environmental determinants, community behaviour, access to healthcare services, and sanitation conditions. In conclusion, the study highlights that the spread of infectious diseases in Medan City is influenced by a variety of interacting factors. Effective prevention and control efforts necessitate a comprehensive, multi-sectoral approach focusing on robust surveillance, community empowerment, improved access to healthcare, and the enhancement of environmental and sanitation conditions.